Low skeletal muscle mass and treatment outcomes among adults with haematologic malignancies: A systematic review and meta‐analysis - Nadia M. Anabtawi; Monica Sai Pasala; Alyssa A. Grimshaw; Prakash Kharel; Susan Bal; Kelly Godby; Ashmita Siwakoti; Thomas W. Buford; Smita Bhatia; Luciano J. Costa; Grant R. Williams; Smith Giri (Wiley, 2024)
Abstract Background Low skeletal muscle mass (LSMM) and/or, function associated with an increased risk of treatment‐related toxicities and inferior overall survival (OS) among adults with solid malignancies. However, the association between LSMM and treatment‐related toxicities among adults with haematologic malignancies remains unclear. Methods Using a pre‐published protocol (CRD42020197814), we searched seven bibliographic databases from inception to 08/2021 for studies reporting the impact of LSMM among adults ≥18 years with a known haematologic malignancy. The primary outcome of interest was OS, and secondary outcomes included progression free survival (PFS) and non‐relapse mortality (NRM). These effect sizes were quantified in terms of hazards ratio (HR) along with 95% confidence interval (CI) and pooled across studies using a DerSimonian-Laird random‐effects model. Heterogeneity was assessed using the Cochran's Q and the I2 statistic. All hypothesis testing was two‐sided with an alpha of 0.05. Results Of 3791 studies screened, we identified 20 studies involving 3468 patients with a mean age of 60 years; 44% were female and the most common malignancy was diffuse large B‐cell lymphoma (42%). Most studies measured muscle mass using single slice computed tomography imaging at the L3 level. The presence of LSMM was associated with worse OS (pooled HR = 1.81, 95% CI = 1.48-2.22, P < 0.001) with moderate heterogeneity (Cochran's Q, I2 = 60.4%), PFS (pooled HR = 1.61, 95% CI = 1.28-2.02, P < 0.001) with moderate heterogeneity (Cochran's Q, I2 = 66.0%). Similarly, LSMM was associated with worse NRM (HR = 1.72, 95% CI = 1.34-2.22, P < 0.001) with little evidence of heterogeneity (Cochran's Q, I2 = 0.0%). Conclusions LSMM is associated with worse survival outcomes among adults with haematologic malignancies. Further research into understanding the underlying mechanism of this association and mitigating the negative effects of LSMM among adults with haematologic malignancies is needed.